Brazilian version of Calgary-Cambridge Observation Guide 28-item version: cross-cultural adaptation and psychometric properties (Clinics, 2021)
OBJECTIVES: The search for appropriate tools to assess communicational skills remains an ongoing challenge. The Calgary-Cambridge Observation Guide (CCOG) 28-item version can measure and compare performance in communication skills training. Our goal was to adapt this version of the CCOG for the Brazilian cultural context and perform a psychometric quality analysis of the instrument. METHODS: Experienced preceptors (35) assessed videos of five medical residents with a simulated patient using the translated guide. For the cultural adaptation, we followed the methodological norms on synthesis, retrotranslation, committee review, and testing. We obtained validity evidence for the CCOG 28-item version using confirmatory factor analysis and the Many-Facet Rasch Model (MFRM). RESULTS: Confirmatory factor analysis indicated an adequate level of goodness-of-fit. The MFRM reliability coefficient was high in all facets, namely assessors (0.90), stations (0.99), and items (0.98). The assessors had greater difficulty with attitudinal items, such as demonstration of respect, confidence, and empathy. CONCLUSIONS: The psychometric indicators of the tool were adequate, a good potential for reproducing its Brazilian version as well as acceptable reliability for its use.